Characteristics of putu ayu a combination of wheat flour and soybeans flour (Glycine max) with the addition of katuk leaves (Sauropus androgynus (L) Merr.) : Karakteristik putu ayu kombinasi tepung terigu dan tepung kedelai (Glycine max) dengan penambahan daun katuk (Sauropus androgynus (L) Merr.) - Anggit Trisnawati; Vivi Nuraini; Merkuria Karyantina (Fakultas Sains dan Teknologi Unisri, 2025)
Putu ayu was traditional Indonesian caked with a soft texture that was a sweet and dominant colour of green. Wheat flour in Indonesian was grew used, so local materials need to be developed to reduce their dependence on wheat flour. This studied aimed to determined of soy flour and extract of katuk leaves which had high antioxidant and preferred consumer. This studied used was two factor Completetly Randomized Design (CRD) with ratio wheat flour and soybeans flour (90:10), (80:20) and (70:30) and extract concentration katuk leaves 10%, 15% and 20%. Putu ayu caked the best treatment was on ratio wheat flour and soy flour (70:30) with extract katuk leaves 15% because had high antioxidant activity 18,35%, aw moistured content 44,99%, ash content 8,35%, total fat 3,53%,8,59% protein, and 9,18% fiber. Soy flour substitutions and the addition of katuk leaves had the potential to increased the protein level of the putu ayu caked.